2016
DOI: 10.4172/2325-9639.1000173
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Sleep Posture and Morning Spinal Symptoms in the Habitual Environment Using Infrared Cameras

Abstract: Introduction: Sleeping is generally considered a period for rest and recovery, however some people wake with spinal symptoms not present on going to sleep and seek treatment. It has been clinically postulated that some sleeping postures, especially those involving sustained end range rotation or extension, can provoke pain sensitive spinal tissues. While sleep research generally has blossomed, little attention has been paid to the physical effects of nocturnal posture on waking spinal symptoms. Furthermore, sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Outcomes of incorrect body position and habits are so grave that negatively affect physical, psychological, social, and economical dimensions [2]. Many studies have shown that abnormal postures (which impose themselves on the spine) would cause sprain, increase or decrease the spine curvatures, reduce efficiency, and exacerbate pain [11]. Also, based on studies, the increase or decrease in lumbar curvatures are the causes of many lumbar pains [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes of incorrect body position and habits are so grave that negatively affect physical, psychological, social, and economical dimensions [2]. Many studies have shown that abnormal postures (which impose themselves on the spine) would cause sprain, increase or decrease the spine curvatures, reduce efficiency, and exacerbate pain [11]. Also, based on studies, the increase or decrease in lumbar curvatures are the causes of many lumbar pains [12].…”
Section: Introductionmentioning
confidence: 99%
“…So far many studies have been conducted regarding the prevalence of spinal abnormalities and its relationship with lumbar pain, body mass, working positions in both workers and clerks, and the nurses' quality of life [1,2,[4][5][6][11][12][13]. However, no study has been conducted on the relationship of the spinal curvatures with resting habits of university students such as sitting position, carrying bag, sleeping, sleeping mattress, sleeping pillow, and especially in the students of the school of rehabilitation who try to acquire information about correct positions and habits in the daily life.…”
Section: Introductionmentioning
confidence: 99%